Drama as a pedagogical tool for practicing death notification-experiences from Swedish medical students - Fjellman-Wiklund Anncristine; Nordström Anna; Grysell Tomas (BMC Medical Education, 2011)
Abstract Background One of the toughest tasks in any profession is the deliverance of death notification. Marathon Death is an exercise conducted during the fourth year of medical school in northern Sweden to prepare students for this responsibility. The exercise is designed to enable students to gain insight into the emotional and formal procedure of delivering death notifications. The exercise is inspired by Augusto Boal's work around Forum Theatre and is analyzed using video playback. The aim of the study was to explore reflections, attitudes and ideas toward training in delivering death notifications among medical students who participate in the Marathon Death exercise based on forum play. Methods After participation in the Marathon Death exercise, students completed semi-structured interviews. The transcribed interviews were analyzed using the principles of qualitative content analysis including a deductive content analysis approach with a structured matrix based on Bloom's taxonomy domains. Results The Marathon Death exercise was perceived as emotionally loaded, realistic and valuable for the future professional role as a physician. The deliverance of a death notification to the next of kin that a loved one has died was perceived as difficult. The exercise conjured emotions such as positive expectations and sheer anxiety. Students perceived participation in the exercise as an important learning experience, discovering that they had the capacity to manage such a difficult situation. The feedback from the video playback of the exercise and the feedback from fellow students and teachers enhanced the learning experience. Conclusions The exercise, Marathon Death, based on forum play with video playback is a useful pedagogical tool that enables students to practice delivering death notification. The ability to practice under realistic conditions contributes to reinforce students in preparation for their future professional role.